Risks factors changes in purchasing style among students of National University of Malaysia during the covid-19 pandemic - Mahirah Mohd Adenan; Roziana Baharin (Pusat Perkembangan Pelajar ,U.K.M, 2022)
In line with the increasingly busy lifestyle changes and the existence of the Covid-19 virus, this new norm of purchasing methods is gaining a place in the hearts of consumers. Online purchases are chosen as an easy step for consumers to limit their movements. The objective of the study was to study the differences in virtual purchasing practices before and during the pandemic. In addition, the study also examines the factors of these changes as well as the risks that will be faced. The population of this study is made up of users among the students at National University of Malaysia who are mostly aged between 19-29 years old. The results of the analysis found an increase in the number of consumers who switched to online purchase patterns during the pandemic. In addition, it is found that the dominant factor that most influences the change is its method of penetrating the world market, being safe and in accordance with the Standard Guidelines & Operations (SOP) as well as having flexibility in terms of time and place. In turn, a bad experience when online trading also affects the behavior of consumers. Hence, positive factors (driving factors) and negative factors (risks) will influence the behavior of the user in making decisions.